Ictal source imaging in epilepsy patients - Supplementary Data - Ye, Shuai; Yang, Lin; Lu, Yunfeng; Kucewicz, Michal; Brinkmann, Benjamin; Nelson, Cindy; Sohrabpour, Abbas; Worrell, Gregory; He, Bin (Dryad, 2020)
Objective Localization of seizure onset zone in focal epilepsy patients is
a crucial step prior to surgical planning. Noninvasively achieving this
goal would have a tremendous impact on clinical management of intractable
seizure. Methods In a total of 39 focal epilepsy patients, we recorded and
extracted 138 seizures and 1,325 interictal epileptic discharges using
high-density EEG. We have investigated a novel approach for directly
imaging sources of seizures and interictal spikes from high density EEG
recordings, and rigorously validated it for noninvasive localization of
seizure onset zone (SOZ) determined from intracranial EEG findings and
surgical resection volume. Conventional source imaging analyses were also
performed for comparison. Results Ictal source imaging showed a
concordance rate of 95% when compared to intracranial EEG or resection
results. The average distance from estimation to seizure onset
(intracranial) electrodes is 1.35 cm in patients with concordant results,
and 0.74 cm to surgical resection boundary in patients with successful
surgery. About 41% of the patients were found to have multiple types of
interictal activities; coincidentally, a lower concordance rate and a
significantly worse performance in localizing SOZ were observed in these
patients. Interpretation Noninvasive ictal source imaging with
high-density EEG recording can provide highly concordant results with
clinical decisions obtained by invasive monitoring or confirmed by
resective surgery. By means of direct seizure imaging using high-density
scalp EEG recordings, the added value of ictal source imaging is
particularly high in patients with complex interictal activity patterns,
who may represent the most challenging cases with poor
prognosis.